MEMPREDIKSI NIAT KEWIRAUSAHAAN: PENERAPAN THE THEORY OF PLANNED BEHAVIOR - Hanif Rani Iswari; Choirul Anam; Wiwin Purnomowati; Survival; Dian Candra Dewi (LPPM Universitas Buana Perjuangan Karawang, 2022)
ABSTRAK Tujuan makalah ini adalah menjelaskan sebab akibat antara theory of planned behavior dengan entrepreneurial intentions. Pendekatan ekplanatory dengan populasi dan sampel mahasiswa Fakultas Ekonomi dan Bisnis Universitas Widyagama Malang sebanyak 220 responden menggunakan teknik random sampling. pengumpulan data menggunakan kuesioner. sedangkan alat analisis menggunakan software Smart-PLS 3. Temuan penelitian pertama menunjukkan bahwa attitude toward entrepreneurship berpengaruh signifikan positif terhadap entrepreneurial intentions. Kedua, subjective norms berpengaruh signifikan positif terhadap entrepreneurial intentions. Ketiga, subjective norms berpengaruh signifikan positif terhadap entrepreneurial intentions Kata kunci: theory of planned behavior, attitude toward entrepreneurship, subjective norms, perceived behavioral control, entrepreneurial intentions ABSTRACT The purpose of this paper is to explain the causation between the theory of planned behavior and entrepreneurial intentions. The explanatory approach with the population and sample of students of the Faculty of Economics and Business, Widyagama University of Malang as many as 220 respondents used random sampling techniques. data collection using questionnaires. while the analysis tool uses Smart-PLS 3 software. The findings of the first study show that attitude towards entrepreneurship has a significant effect on entrepreneurial intentions. Second, subjective norms have a significant effect on entrepreneurial intentions. Third, subjective norms have a significant effect on entrepreneurial intentions Keywords: theory of planned behavior, attitude toward entrepreneurship, subjective norms, perceived behavioral control, entrepreneurial intentions